A System to Generate Robot Emotional Reaction for Robot-Human Communication - zehra nur olgun; YU JUNG CHAE; ChangHwan Kim (2018 15TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS (UR), 2018)
Intelligent system emotion modeling process is dependent on various internal and external. This paper describes an emotional system for intelligent agents, robots specifically, that proposes the idea of emotional learning and generation system to realize human-like emotions in robots. Using basic emotions, a way to construct complex emotions is proposed. Results from experiments indicate that the system has a correlation with perceiving and generating emotions that are parallel with real human emotions.